A Call for Intervention Research to Reduce Event Centrality in Trauma-Exposed Individuals. Issue 1 (2nd January 2021) - Boals, Adriel; Griffith, Elizabeth; Southard-Dobbs, Shana
Abstract: Since the initial paper on event centrality was published by Berntsen and Rubin nearly 15 years ago, there has been a plethora of research demonstrating event centrality as one of the strongest and most reliable correlates of PTSS. Event centrality's ability to predict unique variance in PTSS after controlling for a variety of other factors in cross-lagged studies gives us reason to suspect that event centrality may be a causal factor in the development and maintenance of PTSS. We believe the progression of research on event centrality has reached a critical point, and researchers should turn their attention to attempts to reduce event centrality. A handful of studies have already begun this next line of work, and the preliminary results are encouraging. We argue that Acceptance and Commitment Therapy-based interventions that emphasize the self-as-context process have a strong theoretical rationale for being effective interventions. However, we also acknowledge that there are likely other ways to reduce event centrality, and all reasonable possibilities should be explored. Interventions that are capable of reducing event centrality hold great promise as a supplement to existing treatments for PTSS.